Mechanism of action of phosphodiesterase type 5 inhibition in metabolic syndrome‐associated prostate alterations: An experimental study in the rabbit12. Issue 4 (19th September 2012) - Morelli, Annamaria; Comeglio, Paolo; Filippi, Sandra; Sarchielli, Erica; Vignozzi, Linda; Maneschi, Elena; Cellai, Ilaria; Gacci, Mauro; Lenzi, Andrea; Vannelli, Gabriella B.; Maggi, Mario
Abstract BACKGROUND Phosphodiesterase type 5 (PDE5) inhibitors improve benign prostatic hyperplasia (BPH)‐related lower urinary tract symptoms (LUTS), often associated with metabolic syndrome (MetS). This study investigated the effects of PDE5 inhibition in the prostate of rabbits fed a high fat diet (HFD) for 12 weeks. HFD‐rabbits develop the most important features of human MetS (glucose intolerance, dyslipidemia, increased abdominal adiposity, and hypertension), along with hypogonadism and LUT abnormalities (prostate and bladder inflammation/tissue remodeling). METHODS Gene expression was evaluated by quantitative RT‐PCR. Prostate morphological changes and oxygenation were evaluated by immunohistochemistry. RESULTS HFD prostates showed increased PDE5 expression, suggesting a peculiar sensitivity of prostate to the action of PDE5 inhibitors during MetS. Accordingly, prostate PDE5 mRNA was negatively associated to plasma testosterone/estradiol ratio, whose reduction characterizes MetS, and positively with the expression in prostate of several genes exploring pathogenetic processes for BPH/LUTS, such as inflammation, leukocyte infiltration, and fibrosis/myofibroblast activation. Most of these genes was up‐regulated by HFD, and significantly reduced by PDE5 inhibition, through either chronic (12 weeks) or, at a lower extent, acute (1‐week) tadalafil dosing. Tadalafil was also able to reduce blood pressure and visceral fat in HFD rabbits, without changing any other MetS parameter. Interestingly, 1‐week tadalafil administration to HFD rabbits, significantly blunted prostate inflammation (increased CD45 immunopositivity), fibrosis (reduced muscle/fiber ratio) and hypo‐oxygenation, thus suggesting a potential curative effect of PDE5 inhibition on MetS‐related prostate alterations. CONCLUSIONS Our data provide the experimental evidences to support the multiple potentiality of PDE5 inhibitors as a useful therapeutic tool in LUTS. Prostate 73: 428–441, 2013. © 2012 Wiley Periodicals, Inc.